Ecoriparian Tourism Area Management Model in Special Region of Jakarta - Nugraha, Rizki Nurul; Sunarta, I Nyoman; Ariana, Nyoman; Mananda, I Gusti Putu Bagus Sasrawan (Journal of Posthumanism, 2025)
The management model of the Ecoriparian Tourism Area in the Special Region of Jakarta plays a crucial role in promoting environmental sustainability, preserving local culture, and enhancing the economic well-being of surrounding communities. This research employs a qualitative descriptive approach, utilizing interviews, observations, and focus group discussions. The application of ecotourism in managing the Ciliwung Riverbank area serves as a strategic solution to various river-related issues. Initiatives such as river cruises, fish releases, and tree planting exemplified by the Ciliwung River School—highlight the practical development of ecotourism in the region. Additionally, community-based waste management initiatives, like the establishment of the Ciliwung River Care Community, demonstrate grassroots environmental stewardship. The research’s findings reveal three main outcomes: first, that ecoriparian management significantly contributes to environmental conservation; second, that it offers tangible economic benefits to local communities; and third, that it strengthens the presence and appreciation of local cultural heritage through tourism activities.